Association of diarrhoea and upper respiratory infections with weight and height gains in Bangladeshi children aged 5 to 11 years - Alberto M. Torres; Karen E. Peterson; Ana Cristina T. de Souza; E. John Orav; Michael Hughes; Lincoln C. Chen (The World Health Organization, 2000)
INTRODUCTION: The association between infection and growth delay is not well documented in school-age children in developing countries. We conducted a prospective cohort study to examine the association between infectious disease and weight and height gains among Bangladeshi children. METHODS: A one-year follow-up study was performed to elucidate the determinants and consequences of physical growth of children under five years of age. The study included 135 households randomly selected from four villages in the Matlab area. RESULTS: The most frequent infections were upper respiratory infections (mean = 4 episodes or 27 days per year) followed by non-dysenteric diarrhoea (mean = 2.3 episodes or 15 days per year) and dysentery (mean = 0.2 episodes or 2 days per year). The number of episodes and their duration decreased significantly with age. Over a 12-month period the mean weight gain was 1.3 kg and the mean increase in height was 2.9 cm. The total number of days when diarrhoea occurred was negatively associated with annual weight gain (regression coefficient beta = -7 g per day, P = 0.02), with adjustment for age, sex, energy and protein intake, and household land ownership. The incidence of diarrhoeal disease was significantly associated with weight gain in intermediate models but only marginally associated with it in the final multivariate model (P = 0.08). Neither the incidence nor the duration of upper respiratory infections was associated with weight gain. Height gain was not significantly associated with the duration or incidence of either category of illness. Diarrhoea was a significant correlate of retarded weight gain among children above preschool age, whereas upper respiratory infections were not. DISCUSSION: Diarrhoeal morbidity slowed growth in children well beyond the weaning age, suggesting that increased attention should be given to the study of the continuous impact of diarrhoea in children aged over 5 years. An understanding of the determinants of growth in school-age children in developing countries would maximize the health and developmental outcomes that are the target of international child survival strategies at younger ages.